GRID SYNCHRONIZING THREE PORT DC TO DC CONVERTER FOR SOLAR POWER SYSTEMS - JENISHA ALWIN A; K, Vinukumar (Innovare Journal of Engineering and Technology, 2017)
A three port DC to DC Converter integrating photovoltaic and Battery power for renewable power system is presented in this project. The Converter circuit contains five power Switches, two coupled inductors, and two active clamp circuits. The coupled Inductors are used to achieve high step up voltage gain. Two sets of active clamp circuits are used to improve the system efficiency. Among the three ports one port is connected to the PV source, second port is connected to battery and third one to the load. The solar power is selected as the renewable energy source and battery as the storage device; the battery can either supply the load with the solar energy and at the same time it can store the excess power from the solar panels for backup use. Maximum power point tracking technique is employed to obtain maximum power from PV source. Therefore, the control scheme of the converter provides maximum utilization of PV power most of the time. This converter is suited for renewable power systems which are sourced by solar, wind etc. This converter has merits of high boosting level, reduced number of devices and simple control strategy. The overall system and control schemes are modeled in matlab simulink.